Animal species identification utilising DNAs extracted from traditionally manufactured gelatin (Wanikawa) - Haruki Kuramata; Miho Hashiba; Yuriko Kai; Kazuhisa Nishizawa; Tsuyoshi Inoue; Takane Kikuchi-Ueda; Manabu Uetsuki; Kazuya Yamauchi; Akira Fujisawa; Hiroyuki Oshikane (Heritage Science, 2022)
Abstract Gelatin, sourced from collagen, is an acid-, alkali- or enzymatically hydrolysed product obtained from animal skins and bones. Gelatin has been widely used for the manufacture of various cultural objects, e.g. as a water-soluble binder for dissolving pigments, and as a glue for musical instruments and traditional crafts along with human history. The identification of animal species in gelatin, hence, could provide a critical clue for understanding human history including lifestyles, the culture and the technologies. However, there has been no valid method established to date for identifying the animal species from traditional gelatins. We herein report that the nucleic acids contents (dsDNA, ssDNA and miRNA) from commercially-available gelatins manufactured according to classical procedures (wanikawa) exhibited much higher (about 10 times) than those from modern gelatins made through an industrialised process (yonikawa), suggesting that DNA analysis using the gelatins from cultural assets could be substantially feasible. Moreover, targeting not only commercially available niwaka but also Ukiyo-e, Japanese classical art manufactured through woodblock printings, we here illustrate partial successes in the animal species identification coupled with DNA barcoding technique, hopefully paving the way for scientifically more reliable animal species identifications of archaeological specimens made with a gelatin component.